The Role of Monetary Policy in Turkey During the Global Financial Crisis - Elekdag, Selim (IMF Working Papers; Working Paper ;, 2011)
Turkey is an interesting case study because it was one of the hardest hit emerging economies by the global financial crisis, with a year-over-year contraction of 15 percent during the first quarter of 2009. At the same time, anticipating the fallout from the crisis, the Central Bank of the Republic of Turkey (CBRT) decreased policy rates by an astounding 1025 basis points over the November 2008 to November 2009 period. In this context, this paper addresses the following broad question: If an inflation targeting framework underpinned by a flexible exchange rate regime was not adopted, how much deeper would the recent recession have been? Counterfactual experiments based on an estimated structural model provide quantitative evidence which suggests that the recession would have been substantially more severe. In other words, the interest rate cuts implemented by the CBRT and exchange rate flexibility both helped substantially soften the impact of the global financial crisis.